If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 7y + -7y = 0 + -7y Combine like terms: 7y + -7y = 0 -2x + 0 = 0 + -7y -2x = 0 + -7y Remove the zero: -2x = -7y Solving -2x = -7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = 3.5y Simplifying x = 3.5y
| 4x-16=10x+8 | | 25-(-p+18)=45 | | 120=5x+5(-3x+10) | | 360-59-90-19x= | | 1 = z4– 3 | | h^2-14h+24=0 | | x^2+15x-8=8 | | 2(4x+7)+x= | | 4x-14=42x | | x+16+3x=18+2y | | 8x+3y+24=0 | | fg(-1)=0 | | 15-5/12 | | 4x+56=-6x-194 | | 2p+2=8 | | -g(f)= | | d^2=0 | | 6x2/3=N | | 63+x=10x | | ln(x-4)-ln(x+5)=ln(x-6)-ln(x+6) | | 8y^4-50y^2=0 | | 360-20x= | | 8y^2-50y^2=0 | | 5/x=sin30 | | ln(13X-4)=3 | | -23+6x=73 | | p=3c(c-4) | | 5b=2b-9r | | x/-0.8=8.48 | | v=x(8-2x) | | v=x(8-2x)square | | 9(m+2)=3x+19 |